THE INFLUENCE OF COULOMB REPULSION AND FLUCTUATION EFFECTS ON THE CRITICAL-TEMPERATURE IN LAYERED SUPERCONDUCTORS - (:unkn) unknown (IOP PUBLISHING LTD, 1993)
The influence of the electronic Coulomb repulsion on the critical temperature for a layered superconductor is studied by using the Eliashberg theory. The dependence of the critical temperature, T(c), on the interlayer distances, tunnelling integral t(perpendicular-to) and the thickness of the conducting layers is established. The Lawrence-Doniach free energy functional for quasi-two-dimensional superconductors is used to study the influence of fluctuations of the order parameter phase on T(c) and the dependence of T(c) on t(perpendicular-to) is also obtained. The critical temperature appears to increase with t(perpendicular-to) for T(c) within the range T(c)* < T(c) < T(c0)(2), where T(c0)(2) is the critical temperature formally evaluated by means of BAS theory and T(c)* = (1/T(c0)(2) + 1/2piepsilon(F))-1.
Keywords: HIGH-TC SUPERCONDUCTORS; CARRIER CONCENTRATION; FILMS; SUPERLATTICES; TRANSITION; SYSTEM